The Impact of Colonoscopy Quality Control Table on Adenoma Detection Rates - Bin Deng; Jiehua Zhi; Yaosheng Chen; Lanyu Liang; Jian Wu; Xuefen Gao; Weiming Xiao; Yanbing Ding (Gastroenterology Research and Practice)
Objective. This study aims to investigate the effects of reporting colonoscopy findings and the regular review of outcomes on adenoma detection rates. Methods. Patients who underwent colonoscopy from August 2013 to February 2014 were selected as the intervention group. The preintervention group included patients who underwent colonoscopy from January 2013 to July 2013, in which the procedure sheet for this group of patients was not accomplished. The primary outcome was adenoma detection rate (ADR), and secondary outcomes included the success rate of intubation and withdrawal time. Results. This study included 2,467 cases: 1,302 cases in the intervention group and 1,165 cases in the preintervention group. There was no significant difference in demographic characteristics between the two groups. In the intervention group, withdrawal time of colonoscopy was longer (P<0.01), and the success rate of intubation (92.5% versus 89.1%, P<0.05) and detection rate of polyps (32.6% versus 27.6%, P<0.05) and adenomas (20.0% versus 16.1%, P<0.05) were higher. Significantly high detection rates for proximal adenomas, flat adenomas, and adenomas with a diameter <5 mm were observed in the intervention group (all P<0.01). Conclusion. The reporting and review of procedure details help to improve quality indicators of colonoscopy.